Hand Dominance Is Not of Significance in Performing Fundamental Arthroscopic Skills Simulation Training Tasks - Stephan Reppenhagen, M.D; Roland Becker, M.D; Andreas Kugler, M.D; Dominik John, M.D; Sebastian Kopf, M.D; Hermann Anetzberger, M.D (Elsevier, 2023)
Purpose: To compare the performance of the dominant and nondominant hand during fundamental arthroscopic simulator training. Methods: Surgical trainees who participated in a 2-day simulator training course between 2021 and 2023 were classified, according to their arthroscopic experience in beginners and competents. Only right-handed individuals with complete data sets were included in the study. Ambidexterity was trained using a box trainer (Fundamentals of Arthroscopic Surgery Training, Virtamed AG, Schlieren, Switzerland).Two tasks, periscoping for learning camera guidance and triangulation for additional instrument handling, were performed 4 times with the camera in the dominant hand and then in the nondominant hand. For each task, exercise time, camera path length, and instrument path length were recorded and analyzed. Results: Out of 94 participants 74 right-handed individuals (22 females, 52 males) were classified to novices (n = 43, less than 10 independently performed arthroscopies) and competents (n = 31, more than 10 independently performed arthroscopies). Competents performed significantly better than novices. No significant difference was found after changing the guiding hand for the camera from the dominant to the nondominant hand regarding the camera path length and the instrument path length. Notably, tasks were performed even faster when using the camera in the nondominant hand. Conclusions: Our data demonstrate that the learned manual skills during basic arthroscopic training are quickly transferred to the contralateral side. In consequence, additional fundamental skills training for camera guidance and instrument handling of the nondominant hand are not necessary. Clinical Relevance: For skillful arthroscopy, camera guidance and instrument handing must be equally mastered with both hands. It is important to understand how hand dominance may affect learning during arthroscopic simulator training.